2008
DOI: 10.1529/biophysj.107.108670
|View full text |Cite
|
Sign up to set email alerts
|

Can an Atomic Force Microscope Sequence DNA Using a Nanopore?

Abstract: R. Bension has proposed that single molecules of DNA could be sequenced rapidly, in long sequential reads, by reading off the force required to pull a tightly fitting molecular ring over each base in turn using an atomic force microscope (AFM). We present molecular dynamics simulations that indicate that pulling DNA very rapidly (m/s) could generate large force peaks as each base is passed ( approximately 1 nN) with significant differences ( approximately 0.5 nN) between purine and pyrimidine. These speeds are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Previous analyses of the challenges to polymer sequencing by single molecule force spectroscopy (SMFS), with or without a sliding contact, have focused on DNA sequencing. 22,23 We have shown previously that measurements made with the SCFS approach described here yielded excellent agreement with the predicted positions of aromatic rings substituted into PEG polymers based upon the measured molecular weights of the polymers, 8 and that the CD bead could be used to unzip interactions between the polymer axle and molecules bound to specific sequences within that polymer. 9 Thus the available evidence suggests that SCFS may offer a method for mapping or sequencing long, linear polymers where there are large differences between monomers or blocks, or where specific sequences are recognised by other molecules.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Previous analyses of the challenges to polymer sequencing by single molecule force spectroscopy (SMFS), with or without a sliding contact, have focused on DNA sequencing. 22,23 We have shown previously that measurements made with the SCFS approach described here yielded excellent agreement with the predicted positions of aromatic rings substituted into PEG polymers based upon the measured molecular weights of the polymers, 8 and that the CD bead could be used to unzip interactions between the polymer axle and molecules bound to specific sequences within that polymer. 9 Thus the available evidence suggests that SCFS may offer a method for mapping or sequencing long, linear polymers where there are large differences between monomers or blocks, or where specific sequences are recognised by other molecules.…”
Section: Introductionsupporting
confidence: 66%
“…A check on the applicability of the method may be made by comparing the value of ΔG sl it predicts for ssDNA with the simulated and measured values found by Lindsay and Williams. 10,23 Using calculated values of Φ and P we find predicted values of ΔG sl for the four nucleotides and β-CD to fall between 67 and 76 kJ mol −1 . This is rather larger than the values of ΔG sl calculated using the simulated forces and spring constants reported by Lindsay and Williams 10,23 (31-33 kJ mol −1 ), but as noted above, the experimental data for the sliding of β-CD along ssDNA published subsequently 10 shows force plateaus of approximately 110 pN, corresponding to a ΔG sl of 67 kJ mol −1 which agrees with our prediction.…”
Section: Towards Single Molecule Polymer Sequencingmentioning
confidence: 99%
“… 13 Indeed, steered molecular dynamics (SMD) simulations have shown that small differences in the force required to slip a β-CD over a purine or pyrimidine base could be observed at high loading rate. 40 Two rotaxanes were built with either a 49-base or an 81-base oligonucleotide, each containing two hairpins ( Scheme 4 ). Pulling the β-CD along the PEG–DNA conjugate at high loading rates (∼10–100 nN s –1 ) didn't display any composition-dependent profile and only two rupture events could be observed for each rotaxane.…”
Section: Single Molecule Study By Afmmentioning
confidence: 99%
“…In addition, the force detection method uses optical tweezers to decelerate DNA translocation through nanopores in ionic-current detection [47]. Another proposed approach is based on the di erences of the molecular friction of nucleotides when an ssDNA is pulled through a pore in a substrate [48], or when a tightly tting molecular ring is pulled over an ssDNA [49]. The major di culty of these methods is to thread ssDNA through the pore [48].…”
Section: Introductionmentioning
confidence: 99%